The Bank of Indus: a strategic operational transformation - Rehan Muzamil Butt (International Journal of Experiential Learning & Case Studies)
The case describes how Khyber Bank saw compelling reasons to open branches in FATA, a part of the KPK province. Khyber Bank had only 2.5 months to open branches in FATA, where there was no concept of banking or operating banks in the area. The branches had to be operationalized by the end of November 2019; hence, this was a challenge that was to be encountered by Khyber Bank. In the underdeveloped new zone of FATA, where there was no such idea of the banking system and financial services, recruiting, residence, security, finance, awareness, economic, and infrastructural concerns were real. Despite having the advantage of being the first to market, the bank nevertheless had to ensure that all of its branches were self-sustaining within the first few years of operation. The story was about internal operations and decisions, citizens’ involvement, and analytical study to evaluate the real-world reality of that specific zone. The case explores Khyber Bank’s problems while relocating its branches in FATA within 2.5 months and how they tried to overcome them.